Fluvial and marine deposits in coastal zone: a sedimentological and morphological approach of the Vitoria region, ES - Lourenço Pinheiro, Bruna (Geografares, 2021)
The difficulty in distinguishing between fluvial and marine sands is not uncommon, especially in coastal areas with little sedimentary input and plains very close to the source area. This study aims to characterize the surface sediments of the fluvial-marine plains in the region of Vitória, state of Espírito Santo (ES), and to infer about the depositional processes and the origin of the sands based on the sedimentological (grain size, composition, mineralogy and morphoscopy of quartz grains) and morphological parameters. Sediments were distinguished in sandy and wetland deposits. Despite the textural immaturity, the sandy deposits were classified as fluvial and marine. However, the sedimentological parameters were not sufficient to resolve doubts of provenance in some samples. In this case, the absence of morphological features in sandy deposits or particular shapes such as alignment of sandy ridges are important resources for a paleoenvironmental interpretation, especially when sedimentological parameters appear to be ambiguous.
Keywords: coastal deposits; fluvial and marine sand; morphology